2017
DOI: 10.1016/j.socscimed.2017.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Perceived mHealth barriers and benefits for home-based HIV testing and counseling and other care: Qualitative findings from health officials, community health workers, and persons living with HIV in South Africa

Abstract: mHealth has been proposed to address inefficiencies in the current South African healthcare system, including home-based HIV testing and counseling (HTC) programs. Yet wide-scale adoption of mHealth has not occurred. Even as infrastructure barriers decrease, a need to better understand perceived adoption barriers by stakeholders remains. We conducted focus group discussions (FGD) in South Africa in 2016 with 10 home-based HTC field staff, 12 community health workers (CHWs) and 10 persons living with HIV (PLH).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 39 publications
0
65
0
Order By: Relevance
“…Biometric fingerprint identification was acceptable to all study participants despite focus group caveats about the wide-scale acceptability of biometric identification systems in our population (van Heerden et al 2017). A limitation in drawing conclusions about acceptability is that our sample was relatively small.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Biometric fingerprint identification was acceptable to all study participants despite focus group caveats about the wide-scale acceptability of biometric identification systems in our population (van Heerden et al 2017). A limitation in drawing conclusions about acceptability is that our sample was relatively small.…”
Section: Discussionmentioning
confidence: 89%
“…As noted above, HTC biometric systems have been used for the simpler task of participant verification. Fingerprint identification issues that we encountered underscore the importance of building flexibility into the identification system as recommended by our focus groups (van Heerden et al 2017), especially for fieldwork in resource-poor settings. Luckily, we followed the advice of our focus groups as our study allowed identification through fingerprints, South African IDs, and cell phone numbers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [1,2,4] have suggested that CHWs as a workforce could be beneficial in the South African context. In addition, it is noted that CHWs are considered a dependable vehicle to provide quality contextual health services both in urban and rural settings within the South African context [5]. The South African government has introduced various initiatives to address the historic disparate healthcare system [1].…”
Section: Introductionmentioning
confidence: 99%